MFG-E8 Knockout Aggravated Nonalcoholic Steatohepatitis by Promoting the Activation of TLR4/NF-κB Signaling in Mice - Jun Hu; Hui Du; Yinglin Yuan; Peipei Guo; Junxia Yang; Xinru Yin; Jin Liu; Shengwang Wu; Jingyuan Wan; Xia Gong (Hindawi Limited, 2022)
Nonalcoholic steatohepatitis (NASH) is the common liver disease characterized by hepatic steatosis, inflammation, and fibrosis; there are no approved drugs to treat this disease because of incomplete understanding of pathophysiological mechanisms of NASH. Milk fat globule-epidermal growth factor-factor 8 (MFG-E8), a multifunctional glycoprotein, has shown anti-inflammation and antifibrosis. Here, MFG-E8 was shown to play a key role in NASH progression. Using methionine and choline deficient (MCD) diet-fed mice, we found MFG-E8 knockout exacerbated hepatic damage and steatosis as indicated by increased plasma transaminases activities and hepatic histopathologic change, higher hepatic triglycerides (TGs), and lipid accumulation. Moreover, liver fibrosis and inflammation elicited by MCD were aggravated in MFG-E8 knockout mice. Mechanistically, MFG-E8 knockout facilitated activation of hepatic toll-like receptor 4 (TLR4)/nuclear factor kappa B (NF-κB) signaling pathway in MCD-fed mice. In vitro experiment, the TLR4 specific antagonist TAK-242 rescued palmitic acid- (PA-) primed lipid formation and inflammation in MFG-E8 knockout primary murine hepatocytes. These findings indicated that MFG-E8 is involved in the progression of NASH and the possible mechanism by which MFG-E8 knockout exacerbated NASH in mice is associated with activation of the TLR4/NF-κB signaling pathway.